Implant salvage in breast reconstruction with severe peri‐prosthetic infection. Issue 12 (17th November 2015) - Meybodi, Farid; Sedaghat, Negin; French, James; Keighley, Caitlin; Mitchell, David; Elder, Elisabeth
Abstract: Background: Although treatment of mild peri‐prosthetic infection in implant‐based breast reconstruction results in high rates of resolution, successful management of severe peri‐prosthetic infection remains a significant challenge. Methods: In this case series, a protocol utilizing a novel dressing – negative pressure wound therapy with instillation (NPWTi) – for the management of severe peri‐prosthetic infection in breast reconstruction patients is described. This is an operative technique involving: (i) explantation of the breast prosthesis and application of the NPWTi dressing to the implant pocket; (ii) change of the NPWTi dressing; (iii) intraoperative fluid/tissue cultures; and (iv) reimplantation of the breast prosthesis when cultures yield no growth. Results: This protocol was utilized in six cases of severe peri‐prosthetic infection in five patients with immediate breast reconstruction for breast cancer or risk‐reducing surgery. Cultures of fluid/tissue grew typical and/or unusual organisms. Only one case did not yield an organism. The hospital length of stay upon completion of the protocol ranged from 7–16 days (mean, 12 days). Successful implant salvage was achieved in five of six cases. The protocol was aborted in one case to allow for completion of adjuvant chemotherapy. Conclusions: Early findings from this case series suggest that in cases of severe peri‐prosthetic infection this novel operative protocol may result in successful implant salvage for breast reconstruction patients. Further studies are needed to more fully elaborate the role of NPWTi to achieve implant salvage in challenging cases of peri‐prosthetic infection.